Balanced energy-efficient routing algorithm based on smart antenna and dynamic virtual cluster - Qing-song HU; Li-xin WU; Shen ZHANG; En-jie DING (Tongxin xuebao)
An energy-efficient and energy-consumption-balanced routing,named SaDVC-Routing,was put forward for WSN.The algorithm constructs virtual clusters based on assistant relays in the area of smart antenna beams,and then selects the node with maximum relay weight from the cluster to act as routing relay.With the help of energy consumption and nodes distance information,SaDVC-Routing can dynamically update the virtual clusters with beam expanding.If the beam width exceeds the threshold,a routing request is re-broadcasted based on weighted distance matrix.According to the simulation,it was found that this algorithm could not only decrease the energy consumption,but also get consumption balance between nodes in the local and global area.